Strategic Public Relations in the 130th Anniversary Celebration of RSK Mojowarno - Hermawan, Jessica Nathalia; Wono, Hilda Yunita (Future Science, 2025)
Public relations (PR) plays a crucial role in shaping the reputation of healthcare institutions, particularly in building long-term, value-based relationships with the public. In faith-based hospitals, PR efforts are not only about disseminating information but also about reinforcing institutional identity, trust, and emotional engagement through meaningful communication. This study investigates the public relations strategy employed by RSK Mojowarno during its 130th anniversary, which served as a commemorative moment to amplify the hospital’s presence, introduce new healthcare services, and strengthen its public image by integrating Christian values into its messaging. Rather than treating the anniversary as a ceremonial event alone, the hospital implemented a strategic PR campaign involving participatory activities that aligned with both institutional goals and community interests. The research adopts a quasi-qualitative approach using a case study method. Data were gathered through in-depth interviews with internal stakeholders such as PR staff, human resources personnel, and external community figures, including village leaders. NVivo 15 software was used to assist in thematic coding and analysis, focusing on four dimensions: PR objectives, planning, implementation, and effectiveness. The findings reveal that the strategy centered on three main objectives: promoting healthcare services, reinforcing institutional branding, and engaging with the local community. These were achieved through a series of initiatives such as community health services, blood donation drives, educational seminars, media publication through both digital and offline channels, and collaboration with sponsors and religious institutions. Furthermore, the success of the strategy was measured by event participation, the achievement of program targets, and positive public feedback, especially from social media platforms and direct community responses. The study concludes that commemorative PR, when guided by clear objectives and grounded in institutional values, can serve as an effective approach for enhancing public trust, fostering meaningful relationships, and sustaining a positive institutional image within the healthcare sector.